PEMBELAJARAN BAHASA ARAB MELALUI KEMAMPUAN BACA TULIS AL-QUR’AN PADA SISWA TINGKAT MTs KALIMANTAN TIMUR - luluk HUMAIRO PIMADA (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah, 2019)
The research's goal is to find out the Arabic learning process is based on the ability to read and write the Koran, and what factors influence the learning process of Arabic with the ability to read and write the Koran in students at the Madrasah Tsanawiyah level in the East Kalimamtan. The research isa descriptive qualitative research that tries to describe the process of learning Arabic by using the ability to read and write the Qur'an, the research subjects are 20 educators from the Madrasah Tsanawiyah Institute in the East Kalimamtan. The research instrument was observation, questionnaire, and documentation, data analysis using the Miles and Hubberman Model. The results of the study are the ability to read and write the Koran has an important role in learning Arabic, and one of the abilities that must be possessed by students because this ability is the initial capital in learning Arabic, if students have the ability to read and write the Koran then learning Arabic will be easier to learn and teach. Keywords: Arabic Learning, al-Qur’an Learning, Ability of Reading, and Ability of Writing